Design and characterization of a cobalt-free stainless maraging steel for laser-based powder bed fusion. (November 2022) - Riabov, D.; Frisk, K.; Thuvander, M.; Hryha, E.; Bengtsson, S.
Graphical abstract: Highlights: A Co-free stainless maraging steel for laser-based powder bed fusion was successfully designed using a computation alloy design approach. The material showed excellent printability with a porosity of <0.05% and a fully martensitic microstructure in the as-built condition. Aging at 500 °C was performed directly after printing, where an increase from 310 HV5 to 519 HV5 was noted. Ni, Al, Ti, Nb, Mn and Si were found to readily form precipitates – believed to be γ′ after 3 h. The precipitates were also found to be resistant to coarsening, retaining high hardness even after 90 h at 500 °C. Abstract: This study presents a new Co-free stainless maraging variant for laser-based powder bed fusion developed using a computational alloy design approach. The goal was to develop an easily printable material with similar performance to 18Ni-300. After screening numerous compositions, Fe-13.2Cr-9.1Ni-1.1Al-0.6Mo-0.5Nb-0.23Ti-0.5Mn-0.5Si (wt.%) was selected. This composition showed excellent printability with low porosity levels. The precipitation strengthening response was evaluated by aging at 500 °C for 15 min, 3 h and 18 h, measuring hardness, tensile strength, and by characterization using atom probe tomography. After 15 min of aging, 90% of the maximum hardness was reached, thanks to formation of (Ni, Al, Nb, Ti, Mn, Si) clusters with a density of 1.5 × 10 24 m - 3 . Between 15 min and 3 h, distinct precipitates formed with a radius of ∼1.4 nm. The precipitates underwent a splitting phenomenon after 18 h, forming several unique Ni-rich precipitates including Ni16 Si7 (Ti, Nb)6 and Ni3 (Al, Ti, Nb, Si). The splitting can be a reason for the slow coarsening rate, as the average precipitate radius after 18 h was only 2 nm. Simulations of the precipitation sequence using PRISMA indicated very rapid and dense precipitation of L12 -Ni3 X precipitates with a slow coarsening rate, in agreement with experimental observations.